Invincible iron man (2022), volume 1 ebook Demon in the armor. - Duggan, Gerry (Invincible Iron Man (2022), 2023)
Collects Invincible Iron Man (2022) #1-6 Tony Stark has lost it all. His company, his money - maybe even his sobriety. But Stark doesn't realize he still has so much more to lose, especially when assassins start to come for him! As a familiar foe returns to destroy him once and for all, at least Ironheart is in Tony's corner. But what secret is Riri Williams harboring, and will it change their relationship forever? Soon, another close friend is found dead - and it looks like Tony is the killer. Who is the real murderer? Why are they trying to frame Iron Man? And exactly how far will they go to strike at everything he holds dear? All this, plus Emma Frost! A new armor for War Machine! And the untold story of…Iron Man vs. the West Coast Avengers?!